(untitled) (TAMADDUN NURI JURNALI, 2024)
This study is dedicated to exploring the unique characteristics of traditional clothing that represent the national identity of the Karakalpak people. It examines the distinctiveness of men’s and women’s national outfits, highlighting their differences. During the research process, special attention was given to the patterns, colors, and appearances of Karakalpak national clothing, as well as the meanings they convey and the materials used to make these garments. The scientific analysis of the research topic revealed how the external appearance, colors, and patterns of the Karakalpak national clothing are influenced by the geographical environment, social conditions, and family life, as well as how women’s clothing choices vary depending on age and occasion, reflecting deeper meanings.